G211(P) Better cognitive outcomes for Very Low Birth Weight Infants after implementation of a sepsis reduction care bundle. (7th April 2014) - Davis, JW; Jary, S; Cairns, PA; Harding, D; Luyt, K
Abstract : Background: Published data suggest that very low birth weight infants (VLBW; <1500 g) with late onset sepsis have increased risk of neurodisability. Care bundles to reduce blood stream infections in NICU have been shown to be effective. No studies have demonstrated the impact of these care bundles on long term neurodevelopmental outcome. Objective: To determine if the implementation of a sepsis reduction care bundle was associated with improvement in neurodevelopmental outcomes in VLBW infants. Methods: A sepsis improvement care bundle, based on the Vermont Oxford Network iNIQ package, was implemented in stages in a tertiary level NICU between 2006 and 2007. Mortality and neurological morbidity rates were compared for the pre-intervention (January 2001 to December 2007) and post-intervention (July 2008 to December 2012) periods. We excluded the 6 month period directly following full implementation of the intervention. The highest risk VLBW infants (<30 weeks' gestation) had routine neurodevelopmental assessments at 24 months (corrected for gestation) using the Bayley Scales of Infant development (BSID). Moderate cognitive disability was defined as a cognitive/language score below 2SDs and moderate motor disability as a motor score below 2SDs. The outcome of cerebral palsy (CP) was assessed on neurological assessment at 2 years. Results: Coagulase Negative Staphylococcus septicaemia rates were 7/1000 care days before implementation of the care bundle and from 2009, have reduced year on year to an average of 2.8/1000 care days by 2013. In the cohort of VLBW infants there was no significant reduction in mortality rates (66/426(16%) vs. 40/310(13%); p = 0.3). No significant difference was found in moderate motor disability (17/85(20%) vs. 3/42(7%); p = 0.07) or CP (10/94(11%) vs. 6/49(12%); p = 0.7), before and after the intervention. A significant reduction in moderate cognitive disability (16/86(19%) vs. 2/44(5%); p = 0.03) was found after full implementation of the sepsis care bundle. Potentially confounding variables (birth weight and gender) were not different (p > 0.05) in the pre and post intervention cohorts. Conclusions: This is the first description of the long term impact of a sepsis improvement care bundle on neurodevelopmental outcomes in VLBW infants. The improvement seen in cognitive function at two years of age is likely to translate into significantly less long term learning disability.